STUDI TENTANG SULAMAN INDAH NARAS PADA BAJU PENGANTIN DI KOTA PARIAMAN: MOTIF, PENEMPATAN, DAN MAKNA. - NURMALA OKTAVIANTI, Drs. Erwin, M.Sn, Dra. Ernis, M.Pd (Universitas Negeri Padang, 2015)
Embroidery Beautiful Naras (which is now termed embroidery) has been selected to decorate the wedding dress. Given the events of the bride is a major event at least once a lifetime. Decoration on the wedding dress is not just a function to decorate something to make it look more beautiful. But consideration and messages both in terms of placement or philosophical meaning it contains. But generally people only know the function of clothesjust because of the lack of information describing other functions. Based on these issues conducted a Qualitative research. The results showed at least seven main motif found in placement and philosophical meaning traditional MinangkabauKeywords: motive, placement and meaning